AN GENERAL PERSPECTIVE ON CRM &ITS BENEFITS - SAI SRAVANTHI, GOUNI.; V.RAMANA, DR.D. (IJRDO - Journal of Business Management, 2016)
Customer relationship management (CRM) is a term that refers to practices, strategies and technologies that companies use to manage and analyze customer interactions and data throughout the customer lifecycle, with the goal of improving business relationships with customers, assisting in customer retention and driving sales growth. CRM systems are designed to compile information on customers across different channels -- or points of contact between the customer and the company -- which could include the company's website, telephone, live chat, direct mail, marketing materials and social media.CRM is a strategic approach that integrates people, business and technology to understand the needs of customers to be more satisfied..CRM systems can also give customer-facing staff detailed information on customers' personal information, purchase history, buying preferences and concerns. Customer relationship management (CRM) is a combination of people, processes and technology that seeks to understand a company's customers. It is an integrated approach to managing relationships by focusing on customer retention and relationship development. CRM has evolved from advances in information technology and organizational changes in customer‐centric processes. Companies that successfully implement CRM will reap the rewards in customer loyalty and long run profitability. However, successful implementation is elusive to many companies, mostly because they do not understand that CRM requires company‐wide, cross‐functional, customer‐focused business process re‐engineering. Although a large portion of CRM is technology, viewing CRM as a technology‐only solution is likely to fail. Managing a successful CRM implementation requires an integrated and balanced approach to technology, process, and people.